Chemical Interesterification of Refined Bleached and Deodorised Palm Olein With Palm Methyl Ester - Thang, Yin Mee (2004)
Chemical interesterification using refined, bleached, and deodorised palm olein (POo) as feedstock with fractionated high iodine value palm methyl ester (ME) to produce liquid oil with high iodine value (IV) as well as high monounsaturation was studied. The interesterification has been conducted under different reaction conditions, including ratio of POo to ME, type of catalyst (Na versus NaOMe), catalyst dosage, reaction temperature, and quality of ME (high peroxide value versus low peroxide value) to develop optimum reaction conditions for maximum conversion to increase the unsaturation of the interesterified oil. The reaction is allowed to proceed for two hours before termination. Samples were taken frequently during the course of reaction and subjected to measurement of triacylglycerol (TAG) and diacylglycerol (DAG) distribution. The catalytic performance of interesterification was evaluated by determining changes in the TAG and DAG compositions by reverse-phase high performance liquid chromatography (HPLC), and fatty acid composition by gas chromatography (GC).